Dysregulated Hepatic Expression of Glucose Transporter Type-1, Toll-Like Receptor 4, and Nuclear Factor Kappa B in Estrogen-Induced Cholestasis Pregnant Rats with Placental Ischemia-Reperfusion Stress. Issue 1 (17th January 2022) - Zhou, Fan; Chen, Huafang; Shan, Dan; Wu, Yuxia; Chen, Qian; Hu, Yayi
Abstract: Objective: This study aimed at investigating the expression of nuclear factor kappa B (NF-κB) and mammalian target of rapamycin (mTOR) related signal pathways in liver tissues of intrahepatic cholestasis of pregnancy animal models. Methods: Estrogen (EE)-induced cholestasis and a placental ischemia-reperfusion (IR) model were established in pregnant rats. All pregnant rats were divided into four groups by random number table: EE-IR group ( n  = 6), EE-sham group ( n  = 6), control-IR group ( n  = 6) and control-sham group ( n   =  6). Liver expression of mTOR, its upstream regulator DNA damage response-1 (REDD1), and downstream factor glucose transporter type-1 (GLUT1), accompanied by NF-κB (p65 is the most important component), its activator toll-like receptor 4 (TLR4), and inhibitor IκBα, were detected by western blot analysis and real-time polymerase chain reaction. The intergroup comparisons were performed with a one-way analysis of variance, the comparisons among groups were analyzed with the nonparametric Kruskal-Wallis test. Results: Giving pregnant rats EE alone reduced the hepatic expression of IκBα (0.72 ± 0.20 vs. 1.01 ± 0.07, P  = 0.008). Meanwhile, giving pregnant rats placental IR alone increased liver levels of REDD1 (3.24 ± 0.98 vs. 1.06 ± 0.24, P  = 0.025), GLUT1 (2.37 ± 0.82 vs. 1.09 ± 0.10, P  = 0.039), TLR4 (2.12 ± 0.29 vs. 1.20 ± 0.28, P  = 0.010), and p65 (2.09 ± 0.85 vs. 1.04 ± 0.06, P  = 0.023), and decreased hepatic mTOR (0.50 ± 0.07 vs. 1.01 ± 0.03, P  = 0.001) and IκBα (0.61 ± 0.08 vs. 1.01 ± 0.07, P  = 0.014) expression. Subjecting EE-treated rats to placental IR did not further alter liver levels of GLUT1 (2.02 ± 0.45 vs. 1.79 ± 0.39, P  = 0.240), TLR4 (2.10 ± 0.74 vs. 1.60 ± 0.36, P  = 0.129), or p65 (2.41 ± 0.83 vs. 1.65 ± 0.46, P  = 0.145), whereas it did decrease hepatic mTOR (0.42 ± 0.09 vs. 0.90 ± 0.14, P  = 0.008) and IκBα (0.43 ± 0.09 vs. 0.72 ± 0.20, P  = 0.004) expression and enhance REDD1 expression (4.46 ± 0.65 vs. 2.05 ± 0.47, P  = 0.009). Placental IR stress did impact the hepatic expression of REDD1-mTOR-GLUT1 and TLR4/NF-κB/IκBα in pregnant rats. Conclusion: Placental IR-induced hepatic GLUT1, TLR4, and p65 alternation, which responded efficiently in control rats, were impaired in EE-induced ICP rats.